Pengaruh Penyuluhan CTPS terhadap Peningkatan Pengetahuan Siswa Sekolah Dasar di Kelurahan Sei Mati Medan Labuhan - Arifah Mutiara Irham; Arifa An Nabila; Annisa Aulia Rahmi; Annisa Fijjannah Aliyyah; Annastasya Azzahra; Apsah Pane (Universitas Batanghari Jambi, 2023)
One of the goals of sustainable development (SDGs) in the next 15 years is to overcome health problems that are still found in society today. One of the indicators of Clean and Healthy Living Behavior is Hand Washing with Soap (CTPS) which is a behavior of washing hands using soap to prevent various diseases. There are still many people who think that CTPS is not important, just as they only wash their hands when their hands are dirty. The purpose of this study was to determine whether there was an effect of CTPS counseling on increasing the knowledge of elementary school students in Sei Mati Village, Medan Labuhan. The data collection method used in this study is the WHO rapid survey method with a cross sectional approach, namely research that is carried out in one time only. The type of research used is descriptive quantitative research. By using a one group pretest and posttest design. The subject of this research is the fourth grade elementary school students in Sei Mati Village. Sampling was carried out using the PPS (Probability Proportional to Size) method and Accidental Sampling as many as 210 students. Based on the research results obtained through the results of the pretest and post-test showed a significant level value of p = 0.000 <0.05, it was concluded that there was a difference between the knowledge of the counseling respondents before and after the counseling. With the hope that students can have an awareness of the importance of conducting CTPS activities to prevent the occurrence of various diseases, especially in children